2017
DOI: 10.1002/cssc.201701227
|View full text |Cite
|
Sign up to set email alerts
|

Broadband‐Emitting 2 D Hybrid Organic–Inorganic Perovskite Based on Cyclohexane‐bis(methylamonium) Cation

Abstract: A new broadband‐emitting 2 D hybrid organic–inorganic perovskite (CyBMA)PbBr4 based on highly flexible cis‐1,3‐bis(methylaminohydrobromide)cyclohexane (CyBMABr) core has been designed, synthesized, and investigated, highlighting the effects of stereoisomerism of the templating cation on the formation and properties of the resulting perovskite. The new 2 D material has high exciton binding energy of 340 meV and a broad emission spanning from 380 to 750 nm, incorporating a prominent excitonic band and a less int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
79
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 39 publications
7
79
0
Order By: Relevance
“…2b). 32,[50][51][52] Recently, M. D. Smith et al rationalized the structure/optical properties relationship by examining the ratio between the intensities of the broad emission (I BE ) and the narrow emission (I NE ) in a set of eight <100>-oriented bromide perovskites. 47,53 Within this dataset, it was found that the relative intensity of the broad emission (given by the ratio I BE /I NE ) increases with the increase of out-of-plane distortion of the Pb-(µ-Br)-Pb angle, with the exception of (CEA) 2 PbBr 4 (CEA = cyclohexylammonium) which shows room temperature broadband emission despite the absence of out-of-plane tilt.…”
Section: Broadband Emission In Low Dimensional Perovskitesmentioning
confidence: 99%
“…2b). 32,[50][51][52] Recently, M. D. Smith et al rationalized the structure/optical properties relationship by examining the ratio between the intensities of the broad emission (I BE ) and the narrow emission (I NE ) in a set of eight <100>-oriented bromide perovskites. 47,53 Within this dataset, it was found that the relative intensity of the broad emission (given by the ratio I BE /I NE ) increases with the increase of out-of-plane distortion of the Pb-(µ-Br)-Pb angle, with the exception of (CEA) 2 PbBr 4 (CEA = cyclohexylammonium) which shows room temperature broadband emission despite the absence of out-of-plane tilt.…”
Section: Broadband Emission In Low Dimensional Perovskitesmentioning
confidence: 99%
“…Z. Yuan et al developed a facile one-pot synthesis method to synthesize layered lead(II) bromide perovskite microdisks that exhibited deep blue emissions with PLQEs of up to 53% [94]. Neogi et al reported a 2D perovskite (CyBMA)PbBr 4 (CyBMA: cis-1,3-bis(me-thylamino)cyclohexane) with a broadband emission due to exciton self-trapping ( Figure 5(a)) [95]. Que et al synthesized a novel layered lead iodide, (H 2 Aepz) 3 Pb 4 I 14 , where larger organic cations, bisprotonated 2-(2-aminoethyl)pyrazole (Aepz), were not only sandwiched between the inorganic layers, but also incorporated within the perovskite-like lead iodide layered structure ( Figure 5(b)) [96].…”
Section: D and Quasi-2d Metal Halide Hybridsmentioning
confidence: 99%
“…Despite of their success, there remain critical gaps in chemistry and scope to removal of lead and ligand toxicity. For example, nontoxic ligand–stabilized perovskite nanocrystals are rarely demonstrated in the literature . The installation of nontoxic ligands onto the surface of the perovskite nanocrystals substrate represents a unique synthetic challenge, that if overcome could significantly expand the utility of nontoxic‐based perovskite interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The installation of nontoxic ligands onto the surface of the perovskite nanocrystals substrate represents a unique synthetic challenge, that if overcome could significantly expand the utility of nontoxic‐based perovskite interfaces. Protocols for the synthesis of perovskite nanoparticles with precise sizes and shapes have been finely tuned over years . These methods often involve the use of oleylamine and oleic acid as ligands .…”
Section: Introductionmentioning
confidence: 99%